Mapping the patriarchy in conservation - Leonie Bossert; Tom Crompton; Anwesha Dutta; Joni Seager (npj Biodiversity)
Abstract It is essential to ensure the effectiveness of current conservation efforts to meet the interconnected crises of biodiversity loss, habitat degradation, and climate change. In this article, we discuss one aspect that undermines conservation’s effectiveness while at the same time being underexplored in the academic and political discourse on conservation: patriarchal norms and structures. We argue that these norms and structures, which promote male supremacy and inequality, are central to driving environmental destruction. Many conservation programs unintentionally reinforce patriarchal thinking, thereby undermining their effectiveness. We provide examples of how patriarchy influences conservation, such as the precarious position of women (Working Conditions for Women in Conservation), the treatment of animals (Violence against animals), the suppression of particular forms of knowledge (Science and knowledge production), militarization trends in conservation (Securitization and militarization of conservation enforcement), and the financialization of nature (The monetary valuation of nature). We conclude that patriarchal norms and structures within conservation must be questioned and dismantled to make conservation more effective and just.